ANALISIS BALANCE SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA PERUSAHAAN X - Andika, Ivan Albertus; Chandra, Ivan Christian; Mario, Stefanus (Inaque : Journal of Industrial and Quality Engineering, 2021)
PT X is engaged in the sale of electronic equipment to increase human productivity, such as laptop computers and others, located in Palembang City. The research objective is to analyze and find out how the company is performing using a balanced scorecard. The data source used is in the form of interview data of company leaders, namely the calculation documents of the company leaders that are relevant to the existing research objectives, in the form of company organizational structure, financial reports, notes and questionnaires which are used as the basis for calculating the balanced scorecard. The indicators used in the balance score card include financial, customer, internal business and growth and learning perspectives. The results of the calculation of the balanced scorecard (BSC) show that the performance of Perusahaan X is still said to be not good. Performance still needs to be improved so that the company can achieve excellent performance. We recommend that companies apply a balanced scorecard (BSC) to be able to assist companies in measuring their performance not only from the financial aspect but also considering the performance from non-financial aspects. So that the company can formulate the right strategy before taking long-term action. Keywords: financial perspective, customer, internal business, growth and learning.